Toleransi Minum Enteral Bayi Prematur Menggunakan Spuit 20 Ml dan Spuit 50 Ml - Elfira Awalia Rahmawati; Yeni Rustina; Defi Efendi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the comparison of enteral drinking by using syringes of 20 ml and 50 ml of drinking tolerance in preterm infants. The method used is a randomized controlled trial with a crossover design. The results of this study illustrate that there is a significant difference in the duration of the drinking intervention intervention group using 20 ml syringes and 50 syringes on the first and second day (p value respectively 0.036; 0.033), there is no significant difference in the intervention group giving drinking using 20 ml syringe and 50 ml syringe on the third day (p value 0.984). There were no significant differences in gastric residue on the first, second and third day in the two intervention groups. The incidence of vomiting on the first, second and third day there was no significant difference in the intervention group of drinking using a 20 ml syringe and 50 ml syringe (p value each was 1,000). Conclusion, Provision of enteral drinking by using a 20 ml syringe and 50 ml syringe have the same drinking tolerance in premature babies. Keywords: Premature Babies, Enteral Drinking, Tolerance to Drink